Retrospective analysis of premedication, glucocorticosteroids, and H1-antihistamines for preventing infusion reactions associated with cetuximab treatment of patients with head and neck cancer. (August 2017) - Ikegawa, Kiwako; Suzuki, Shinya; Nomura, Hisanaga; Enokida, Tomohiro; Yamazaki, Tomoko; Okano, Susumu; Endo, Kazushi; Saito, Shinichiro; Yamaguchi, Masakazu; Tahara, Makoto
Objectives: We evaluated infusion-related reactions associated with cetuximab combination chemotherapy comprising an H1-receptor antagonist plus dexamethasone as anti-allergy premedications for patients with head and neck cancer. Methods: We retrospectively evaluated 248 patients who received a cetuximab combination regimen between December 2012 and August 2015. All patients received 5 mg intravenous dichlorpheniramine (H1-receptor antagonist), and dexamethasone (DEX) was adjusted from 6.6 mg to 13.2 mg according to the emetogenic risk. Results: We identified 248 subjects, including 13 (5.2%) with infusion-related reactions (grade 1 in five [2.0%], grade 2 in seven [2.8%], and grade 4 in one [0.4%]). The incidence of these reactions in cetuximab combination regimens, each employing an H1-receptor antagonist, using a higher dose of dexamethasone (13.2 mg) was not significantly lower compared with those using 6.6 mg DEX (2.4% vs 8.3%, respectively; p = 0.43). Twelve patients experienced infusion-related reactions associated with the first cetuximab administration, and one reaction occurred after the third administration. Conclusions: The incidence of infusion-related reactions was lower compared with those of previous studies. Dexamethasone combined with an H1-receptor antagonist was useful for preventing allergic responses. The incidence of infusion-related reactions was not lower with 13.2 mg dexamethasone, and 6.6 mg DEX prevented infusion-related reactions.